The Effects Of Heating And Cooling Energy Piles Under Working Load At Lambeth College, UK - Tony Amis (Deep Foundations Institute, 2008)
There is very limited information relating to the potential impact of temperature cycles, outside the variation that occurs naturally, on the behaviour of foundation piles. Such thermal loading occurs when piles are used as heat exchange elements within a Ground Sourced Heat Pump system, in addition to carrying building loads to competent strata. An investigation has been undertaken where a conventional load test has been extended to include a period in which the load is maintained and temperature cycles applied. Instrumentation was installed in the test pile, an adjacent borehole, two of the anchor piles and the heat sink pile in order to be able to develop an understanding of the temperature variation and associated strain changes within and between the various elements. Conventional electronic strain and temperature gauges have been used in conjunction with optical fibre sensors which also measure strain and temperature changes. The results have confirmed the validity of the assumption made in the thermo-dynamic design of the system, the compatibility of the differing measurement systems and differing installation methods for the optical fibres, and initial assessment suggests that the load-settlement response of the pile is not adversely affected by the temperature cycles applied.